2010
DOI: 10.1055/s-0030-1250405
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Published in 2009 from Plants Traditionally Used to Treat Malaria

Abstract: Malaria is a major parasitic disease and is responsible for almost one million deaths each year in Africa. There is an urgent need to discover new active compounds. Nature and particularly plants are a potential source of new antimalarial drugs since they contain a quantity of metabolites with a great variety of structures and pharmacological activities. This review covers the compounds with antiplasmodial activity isolated from plants which have been published during 2009 organized according to their phytoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…The IC 50 values for these compounds were in the μ M range as it has been reported for other STLs [12] and particularly for pseudoguaianolides such as helenalin and its ester derivatives [13]. …”
Section: Resultssupporting
confidence: 59%
“…The IC 50 values for these compounds were in the μ M range as it has been reported for other STLs [12] and particularly for pseudoguaianolides such as helenalin and its ester derivatives [13]. …”
Section: Resultssupporting
confidence: 59%
“…However, the last review on anti-malarial compounds from African flora dates back about ten years [13], with other reviews focusing on plant-screening campaigns in particular regions and/or countries in Africa [15-35] or on active compounds obtained by bioassay-guided fractionation efforts from given countries and/or regions, not covering an entire continent [36-41]. Even though natural products that are active against P. falciparum have been discussed in a number of review papers [1,42-48], the goal has been to provide an coverage of the most promising anti-malarials from the entire African continent, by giving an overview of the most pertinent in vitro and in vivo screening results reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Nkunya et al (1991) described a study of nine species of Uvaria in which the following antimalarial substances were isolated: uvaretin, diuvaretin and (8',9'-dihydroxy)-3-farnesylindole (IC 50 = 3.5, 4.2 and 2.7 μg/mL, respectively, against the K1 strain of P. falciparum. In their review on natural products from traditionally used antimalarial plants, Bero and Quetin-Leclercq (2011) reported that the antiplasmodial substance (+)-3-acetylaltholactone was isolated from the extracts of the flowers of Goniothalamus laoticus Bân and exhibited in vitro activity against the K1 strain of P. falciparum (IC 50 = 9.5 μM). In vivo activity was observed for another Annonaceous species, Annickia chlorantha (cited as Enantia chlorantha), which is found in Nigeria and other parts of West Africa.…”
Section: Xylopiamentioning
confidence: 99%